Outpatient health care 30 days after hospitalization for heart failure in France. (13th November 2019) - Lesuffleur, T; Feldman, S; Tuppin, P; Constantinou, P; Olié, V; Jullière, Y
Abstract: Background: Recommendations for heart failure (HF) outpatient follow-up have been published. The SNDS offers the opportunity to confront them to real-life, including geographical disparities. Moreover, estimation variation has to be explored when population excludes institutionalized patients (IP) that have specific healthcare use and refund: rehabilitation (SSR), psychiatric hospitalization (psy), skilled nursing home (EHPAD) which is not usually done.The Purpose is to study outpatient healthcare use variations in France after hospitalization for HF, using SNDS data. Methods: The first stay for HF (>0days) in 2015 of patients over 18 yo covered by the general scheme (RG/SLM 88% of population) was considered. Healthcare use 30 days after was compared with (RG/SLM) or without IP (RG/SLM eIP). Regional outpatient care use rates were standardized by age and sex. Results: Among 104 984 alive patients 30 days after HF hospitalization (RG/SLM, female 52%, mean age 79 yo), 16% stayed in SSR, 9% in cardiologic SSR, 12% in EHPAD, 0.2% in psy and 75% returning home and not institutionalized (RG/SLM eIP; n = 70367). Among all RG/SLM patients vs RG/SLM eIP (mean age 79 yo vs 78 yo), a cardiologist was seen at least once in 30 days post hospitalization 20% vs 21% (median delay 14 days IQR 7-23 vs 16 IQR 9-24), a general practitioner 69% vs 78% (8 IQR 3-16 vs 7 IQR 3-15), a nurse 58% vs 69% (3 IQR 1-9 vs 2 IQR 1-7). ACE inhibitors were reimbursed at least once for 34% vs 39%, ARBs 14% vs 17%, and diuretics 69% vs 77%. Among RG/SLM eIP patients, departmental disparities were high: cardiologist (3% to 46%), GP (59% to 93%), nurse visit (49% to 82%). Lower rates for GP were found in the center of France but with higher rates for nurse visits. Conclusions: We recommend using RG/SLM eIP when studying outpatient healthcare use in the SNDS. Low visit rates and high delays regarding the recommendations point out the need of a multidisciplinary community health care in France. Key messages: Low visit rates and high delays regarding the recommendations point out the need of a multidisciplinary community health care in France. We recommend using RG/SLM eIP when studying outpatient healthcare use in the SNDS.